Zasada sprawnej egzekucji sądowej jako element efektywnego wymiaru sprawiedliwości - Derlatka, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The principle of effective judicial protection constitutes an element of the EU law, the Convention system and is found in national systems. The right to a court is a fundamental element of effective legal protection (Article 47/1 of the Charter of Fundamental Rights of the European Union, Article 6, Paragraph 1 of the Convention for the Protection of Human Rights and Fundamental Freedoms). The principle of effective enforcement is the essence of the right to a court. Efficient execution enhances citizens’ confidence in the law. According to the Constitutional Court, the execution of a court ruling is an integral part of the trial. Examination proceedings constitute the so-called “preliminary stage”, and the execution serves the proper implementation of effective judicial protection. Enforcement proceedings serve the fulfillment of the creditor’s claims, which he has not been able to obtain on a voluntary basis. The principle of effective enforcement fully serves the interests of the creditor, not the debtor. Court enforcement, which is the essence of enforcement proceedings, should be conducted in a fast and efficient manner. The efficiency of enforcement is ensured by enforcement bodies, i.e. bailiffs and courts, coercive measures provided for by the law of civil procedure. The principle of the right to a court (Article 45, Paragraph 1 of the Constitution of the Republic of Poland) and the principle of democratic rule of law (Article 2 of the Constitution of the Republic of Poland) protect the execution of final judgments. Enforcement proceedings is distinguished by the operation of two main principles of civil proceedings, i.e. the principle of formalism and availability.